The Impact of Sugar-Sweetened Beverage Consumption on the Liver: A Proteomics-Based Analysis - Benade, Janina; Sher, Lucien; De Klerk, Sheneez; Deshpande, Gaurang; Bester, Dirk; Marnewick, Jeanine L.; Sieck, Gary; Laher, Ismail; Essop, M. Faadiel (Antioxidants, 2020)
Cardiometabolic complications such as the metabolic syndrome and Type 2 Diabetes Mellitus (T2DM) are major causes of global morbidity and mortality. As sugar-sweetened beverages (SSBs) are implicated in this process, this study aimed to obtain greater mechanistic insights. Male Wistar rats (~200 g) were gavaged with a local SSB every day for a period of six months while the control group was gavaged with an iso-volumetric amount of water. Experimental dosages were calculated according to the surface area-to-volume ratio and were equivalent to 125 mL/day (in human terms). A proteomic analysis was performed on isolated liver samples and thereafter, markers of endoplasmic reticulum (ER) stress, antioxidant/oxidant capacity, calcium regulation, and mitochondrial functionality were assessed. These data show that SSB consumption resulted in (a) the induction of mild hepatic ER stress; (b) altered hepatic mitochondrial dynamics; and (c) perturbed calcium handling across mitochondria-associated ER membranes. Despite significant changes in markers of ER stress, the antioxidant response and calcium handling (proteomics data), the liver is able to initiate adaptive responses to counteract such stressors. However, the mitochondrial data showed increased fission and decreased fusion that may put the organism at risk for developing insulin resistance and T2DM in the longer term.